PENGARUH PEMBERIAN TIMBAL (Pb) ASETAT PERORAL TERHADAP KADAR GLUKOSA DARAH PADA MENCIT (Mus Musculus)JANTAN Balb/C - Jayanti, Neti Eka (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Several  kind  of  heavy  metals  that  present  in  the  environment  are  considered  as  toxic  substance to human and animal. Lead (Pb) is one of   heavy metals that increase in use for  the  last  decade.  Lead  toxicity  to  human  had  wide  in fluence  in  medical  aspect,  from  nerve  problem, bone metabolics disturbance until liver an d renal failure. This experiment tried to  found out the effect of cronic oral lead consumtion to lead plasma rate in mice. Design of  this  experiment  is  true  research  experiment  to  test   wheater  there  is  an  effect  of  oral  lead  consumption  to  acumulation  of    lead  in  blood glucose   of  mice.  The results show increase of lead  accumulation in blood glucose of the mice compared to control group.